Temporal patterns in the diet and food partitioning in Imperial Cormorants (Phalacrocorax atriceps) and Rock Shags (P. magellanicus) breeding at Bahía Bustamante, Argentina - Punta, Gabriel; Yorio, Pablo Martin; Herrera, Gonzalo (The Wilson Bulletin)
We studied the diet of Imperial Cormorants (Phalacrocorax atriceps) and Rock Shags (P.magellanicus) at Bahý´a Bustamante, Argentina, between 1992 and 1994. We analyzed pellet casts (1887 from Imperial Cormorants and 799 from Rock Shags) and regurgitations of stomach contents (260 from Imperial Cormorants and 24 from Rock Shags). Imperial Cormorants and Rock Shags fed on at least 22 and 21 different types of prey, respectively. The main prey species during all study years were fish: Engraulis anchoita for Imperial Cormorants and Patagonothen sp. for Rock Shags. For both species, the consumption of the main food categories as estimated by pellet analysis was similar among years. A significant relationship was found between Imperial Cormorant and Rock Shag diets during the three years, while the diet overlap index was relatively high. During all years, Imperial Cormorants consumed a significantly larger proportion of pelagic or demersal fish than did Rock Shags, while Rock Shags consumed benthic fish in a greater proportion than did Imperial Cormorants. Mean maximum diving depth, determined using capillary tube depth gauges, of Imperial Cormorants (24.4 m 6 18.8 SD) was significantly greater but more variable than that of Rock Shags (9.3 m 6 4.1 SD). Fil: Punta, Gabriel. Dirección General de Intereses Marítimos y Pesca Continental, Chubut; Argentina Fil: Yorio, Pablo Martin. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina. Wildlife Conservation Society; Estados Unidos Fil: Herrera, Gonzalo. Dirección General de Intereses Marítimos y Pesca Continental, Chubut; Argentina